2008
DOI: 10.1186/1471-2202-9-112
|View full text |Cite
|
Sign up to set email alerts
|

The Kv2.1 K+ channel targets to the axon initial segment of hippocampal and cortical neurons in culture and in situ

Abstract: Background: The Kv2.1 delayed-rectifier K + channel regulates membrane excitability in hippocampal neurons where it targets to dynamic cell surface clusters on the soma and proximal dendrites. In the past, Kv2.1 has been assumed to be absent from the axon initial segment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 37 publications
5
82
0
Order By: Relevance
“…It should be noted that only GFP-Kv2.1 vesicles appeared in the axon (Fig. 5C, arrow), consistent with the localization of Kv2.1 in the axon initial segment (9,26). These data demonstrate that neurons strictly sort GFP-Kv2.1 and mCherryKv4.2 into different populations of transport vesicles at the Golgi apparatus.…”
Section: Probing Post-golgi Traffic In Neurons By Live Cell Imaging-supporting
confidence: 58%
“…It should be noted that only GFP-Kv2.1 vesicles appeared in the axon (Fig. 5C, arrow), consistent with the localization of Kv2.1 in the axon initial segment (9,26). These data demonstrate that neurons strictly sort GFP-Kv2.1 and mCherryKv4.2 into different populations of transport vesicles at the Golgi apparatus.…”
Section: Probing Post-golgi Traffic In Neurons By Live Cell Imaging-supporting
confidence: 58%
“…Previous studies have indicated that neuronal I K channels are composed of ␣-subunits of the Kv2 subfamily. In particular, Kv2.1 subunit, which is highly expressed in most mammalian central neurons, is a major contributor to I K channels and plays a crucial role in regulating neuronal excitability (Sarmiere et al, 2008). Recent studies confirmed by polymerase chain reaction (data not shown) have indicated that Kv2.1 is a major component of cortical neuron I K channels (Guan et al, 2007).…”
Section: Amoxapine Inhibited I K 443mentioning
confidence: 90%
“…Another K + channel that localizes to ER-plasma-membrane junctions (or SSCs) is the primary delayed-rectifier K + channel in the mammalian brain, Kv2.1 (also known as KCNB1). Kv2.1 regulates the action potential frequency in a wide variety of neuronal cell types in the mammalian brain, but it also displays an intriguing membrane localization pattern of micron-sized cell-surface clusters over the soma, proximal dendrites and axon initial segment in the intact brain and in cultured neurons (Lim et al, 2000;Sarmiere et al, 2008). The clustered phenotype can be recapitulated heterologously in transfected HEK cells (O'Connell et al, 2006;Tamkun et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Kv2.1 clusters also represent ER-plasma-membrane junctions within the axon initial segment Kv2.1 clusters form within the axon initial segment, where localization of voltage-gated Na + channels is necessary for the initiation of axon action potentials (Sarmiere et al, 2008). Because Kv2.1 clusters are often adjacent to RyRs at the axon initial segment (King et al, 2014) we examined the relationship between Kv2.1 clusters and the DsRed2-ER marker at the axon initial segment in cultured rat hippocampal neurons, as illustrated in Fig.…”
Section: Camentioning
confidence: 99%